Alhuqûl ad dalâliyah bayna al musthalahât al mutarâdifah wa atsaruhâ fî fahmi alqur’ân - Moh. Ismail (At-Ta'dib, 2017)
One of the superiority of the Al-Qur'an is the accuracy of the meaning of words. And to understand the true meaning of the structure of the Qur'an can be done by detecting the phenomenon of language, including the phenomenon of equations and the relationship between the meaning of words. The equation of meaning in the Al-Qur’an is a broad subject, so it takes great effort in analyzing the meaning of synonyms, the most important being the analysis of the original meaning to the analysis of the structure context, and the semantic relationship between the two. The semantic relationship is the basis of communication and understanding among members of human society and in understanding the meaning of the words of the Al-Qur'an, this is the essence of linguistics and what is the purpose of the study of sound, morphology and grammar. This research takes words that have synonyms as an example of research, namely الدين ,الملة  , العلم and  المعرفة. The researcher's view that the words " الدين" and " الملة" indicate shari'a and obedience to God, which is a kind of cognitive meaning, Science is more general than knowledge, whether related to truth, goodness, al-Qur'an, livelihood, kindness, , and mind. The effect of the semantic relationship between synonyms is the interpreter's understanding, which is a linguistic influence. We see that interpreters begin to simultaneously articulate words, synonyms, meanings, widening meanings, narrowing meanings, linguistic differences, verbal joints, derivatives and the context. Includes curriculum for al-Zamzhari, al-Tabri and Ragheb al-Asfahani.